ANALISIS HAMBATAN PELAKSANAAN PUAP (PENGEMBANGAN USAHA AGRIBISNIS PEDESAAN) DALAM UPAYA PENINGKATAN KESEJAHTERAAN PETANI PENGGARAP (Studi pada Gapoktan Desa Sriagung Kecamatan Padang Ratu Kabupaten Lampung Tengah) - Pusparini, Astria Devi; Fatimaningsih, Endry (JURNAL SOSIOLOGI, 2013)
PUAP is part of the implementation program PNPM Mandiri-through the help of venture capital in agribusiness ventures in accordance with grow up the potential of the agricultural village of target. Such a program is in the village of PUAP Sriagung Padang Queen who becomes the location of the research, but in execution there are obstacles PUAP cause not a maximum goal achievement program PUAP. The purpose of the research is to identify and explain barriers to the implementation of the welfare improvement efforts PUAP farmer peasants in the village of Sriagung sub-district of Padang Ratu. Research methods used are qualitative research methods. Engineering data collection using in-depth interviews, literature studies and documentation studies.Â The results showed that the barriers implementation of internal factors namely PUAP include loan repayment delays, weak institutional gapoktan, remittances have not been evenly distributed, human resources are limited, and to factor in eksern, i.e. a factor of nature and culture of dependency. Thus, the need to do a little extra accompaniment, to control all implementation PUAP, ranging from planning, drafting activities, counseling, mentoring, channelling funds PUAP, and reporting, all parties concerned must be meningkatkn performance, so that the assistance provided actually helped the farmers to increase the welfare of her life.Â Keywords: resistance, PUAP, gapoktan